Berpikir Kritis Matematis Siswa dalam Menyelesaikan Soal AKM Numerasi Konten Geometri dan Pengukuran Ditinjau dari Gaya Kognitif - Suwito, Gita Ramdani; Susanah, Susanah (Universitas Negeri Surabaya, 2024)
This study aims to describe students' critical thinking in solving AKM Numeracy Geometry Content and Measurement problems based on Field Independent and field dependent cognitive styles. The subjects of this study were one field-independent cognitive-style student and one field-dependent cognitive-style student who had the same sex and an equivalent level of mathematical ability. The instruments used are cognitive style tests, AKM question assignments and interview guidelines. The results of this study show that field independent cognitive style students meet all critical thinking indicators in solving AKM numeracy geometry content and measurement problems which are divided into six aspects of skills, namely interpretation, analysis, evaluation, inference, explanation and self-regulation, while field dependent cognitive style students only meet some critical thinking indicators contained in the evaluation aspect, inference and explanation.